Fighting for a Radical City: Student Protesters and the Politics of Space in 1960s and 1970s Downtown Manhattan - Beasley, Betsy (Urban History Review / Revue d'histoire urbaine, 2009)
AbstractIn the popular imagination, 1960s radicalism often appears as a national phenomenon that varied little from region to region. The case of downtown Manhattan during these years, however, challenges this assumption. Student radicals at New York University in Greenwich Village were just as concerned with issues of urban equity and the politics of urban space as they were with more national concerns, such as ending the Vietnam War. NYU students advocated that the university offer open admissions and free tuition to any New Yorker who wished to attend and fought against what they perceived to be the university’s imperialistic management of Bellevue Hospital.In this paper, I consider the ways in which late 1960s radicals in downtown Manhattan negotiated how a city should be constituted, and I argue that, in challenging the concrete city conditions that they deemed to be indicative of larger systemic problems, these radicals’ activism represents not only a piece of 1960s radical history but also a chapter of local urban history. Manhattan radicalism in the 1960s was predicated on the urban environment that it was a part of, and a consideration of the radical efforts to reconstruct the postwar city is essential to understanding period radicalism and the development of cities.The rapid and transformative changes in American metropolitan areas after the Second World War and the leftist radicalism that is the hallmark of the decade are narratives that commentators often tell as two different, unrelated stories, even though, in the case of New York City, student activism had everything to do with the postwar city. My examination of radicals’ work to enact local change takes steps toward furthering the efforts of a generation of scholars who have tried to complicate our view of “the sixties.”